Psychotropic Drugs for Older Adults With Psychiatric Disorders Presenting to the Emergency Department: Prescription Patterns and Treatment Outcomes - Marianna Mazza; Marcello Covino; Francesco Maria Lisci; Caterina Brisi; Georgios D. Kotzalidis; Giuseppe Marano; Francesca Abate; Maria Benedetta Anesini; Gianluca Boggio; Michele Ciliberto; Valeria De Masi; Cecilia Falsini; et al. (Psychiatric Research and Clinical Practice)
Objective A high proportion of patients presenting to Emergency Departments (EDs) consists of vulnerable elderly people. Mental illnesses are frequently related to advancing age, with difficult to detect symptoms. The aim of this study was to investigate psychiatric drug use by geriatric patients in an ED for whom a psychiatric consultation was needed, according to their psychopathology and severity of outcome. Methods During 2014 to 2023, 342 aged patients (35.96% men and 64.04% women; median age = 73 years, range 68–79 years) sought help at the ED of our hospital and required psychiatric consultation. Results Male sex, nonsuicidal self‐harm, and access through emergency medical services were predictors of >48‐h ED stay/hospital admission (the main severity outcome). Patients with bipolar disorder (BD) and psychotic disorders were more socially disadvantaged and with significantly longer length of stay at the ED than the other groups. Additionally, BD patients had more psychiatric drug prescriptions at discharge than patients in the other diagnostic groups. Current nonsuicidal self‐harm emerged as a predictor of >48‐h ED stay/hospital admission. Conclusions Future studies should focus on investigating suicide risk in ED contexts, on correct diagnosing and on prescription appropriateness of medications in older adults with psychiatric disorders referring to the ED so to tailor‐cut treatment on individual patients' needs. Relevant to Clinical Practice This study highlights the significant impact of psychiatric conditions on healthcare utilization among elderly patients presenting to the ED. The findings emphasize the need for improved diagnosis and management of psychiatric disorders, medication optimization, and tailored treatment approaches.